Effects of Salicylic and Gibberellic Acids on Wheat (Triticum Aestivum L.) Under Salinity Stress (Bangladesh Journal of Botany, 2012)
Salinity decreased seed germination, the length, fresh and dry weight of the root and shoot, chlorophyll and carotenoid contents of wheat. The proline content was increased by salinity. The application of salicylicand gibberellic acids, was found to alleviate the adverse effects of salinity stress on the above parameters. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11079Bangladesh J. Bot. 41(1): 29-34, 2012 (June